2011
DOI: 10.4103/0975-9476.82523
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials of metals in ancient India: A review through Charaka Samhita

Abstract: The Ayurvedic system of medicine has stood the test of time for four millennia or more. The ancient seers found that drugs of different origin (herbal, metal or animal) in addition to codes of conduct and dietary regulations are suitable tools to maintain health in healthy and eradicating diseases in diseased. Use of metallic preparations in healthcare is a unique feature in this system. Processed metals including Mercury, Gold, Silver, Lead, Zinc, Copper etc. were used very frequently by seers of the Indian t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 4 publications
0
57
0
Order By: Relevance
“…The Rasashastra of the Ayurvedic system of medicine deals with medicines of mineral origin. 3 The properties of metal nanoparticles have been widely studied for their antimicrobial activity. Metal nanoparticles such as silver oxide (Ag2O), titanium dioxide (TiO2), silicon (Si), copper oxide (CuO), zinc oxide (ZnO), gold (Au), calcium oxide (CaO) and magnesium oxide (MgO) have demonstrated antimicrobial activity against a spectrum of microorganisms.…”
mentioning
confidence: 99%
“…The Rasashastra of the Ayurvedic system of medicine deals with medicines of mineral origin. 3 The properties of metal nanoparticles have been widely studied for their antimicrobial activity. Metal nanoparticles such as silver oxide (Ag2O), titanium dioxide (TiO2), silicon (Si), copper oxide (CuO), zinc oxide (ZnO), gold (Au), calcium oxide (CaO) and magnesium oxide (MgO) have demonstrated antimicrobial activity against a spectrum of microorganisms.…”
mentioning
confidence: 99%
“…Through process of purification and processing, the metals are becoming biocompatible. In the herbo-mineral preparations, the metals are transforming into very potent drugs [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The ancient seers of Ayurveda had found that drugs of different origin (herbal, metal, or animal) in addition to codes of conduct and dietary regulations were suitable tools to maintain health in healthy and eradicating diseases in diseased person. [7] The use of metallic preparations in healthcare is a unique feature in this system. Processed metals (mercury, gold, silver, lead, zinc, copper, etc.…”
Section: Review Articlementioning
confidence: 99%